Estimation of the Efficiency of Corrosion Inhibition by Zn-Dithiocarbamate Complexes: a Theoretical Study - Kadhim , Mustafa M.; Juber, Layla A. Al.; Al-Janabi, Ahmed S. M. (Iraqi Journal of Science, 2021)
Seven Zn-dithiocarbamate complexes were suggested as corrosion inhibitors. Density functional theory (DFT) was used to predict the ability of inhibition. Room temperature conditions were applied to suggest the optimization of complexes, physical properties, and corrosion parameters. In addition, the HOMO, LUMO, dipole moment, energy gap, and other parameters were used to compare the inhibitors efficiency. Gaussian 09 software with LanL2DZ basis set was used. Total electron density (TED) and electrostatic surface potential (ESP) were utilized to show the sites of adsorption according to electron density.